R-R interval variation and sympathetic skin response in Fibromyalgia - Ozgocmen, S; Yoldas, T; Yigiter, R; Kaya, A; Ardicoglu, O (Elsevier Science Inc, 2006)
Background. This study proposed to assess the autonomic nervous system (ANS) functions in fibromyalgia (FM) by using two electrophysiological tests, sympathetic skin response (SSR) and the heart rate variability named R-R interval variation (RRIV). Methods. Sympathetic skin response and RRIV were studied in 29 female patients with FM and 22 healthy age-matched female controls. R-R interval variation at rest (R%), during deep breathing (D%), the difference between D% and R% (D-R) and the ratio of D-R% (D/R) were determined. Pain threshold was measured using a mechanical algometer. Results. R-R interval variation at rest (R%) and D/R did not show significant difference between patients and controls, whereas D% and D-R were significantly lower in patients compared to controls. SSR latencies of patients' hands and feet had no significant difference compared to controls' hand and feet SSR latencies. SSR latencies of patients' hands correlated significantly with control point score, total myalgic score, Hamilton Anxiety Rating Scale (HARS) and Hamilton Depression Rating Scale. Sympathetic skin response latencies of patients' feet correlated only with HARS. Conclusions. Analysis of heart rate variability may be useful and complementary to clinical examination in patients with symptoms of dysfunction in cardiovascular reflex pathways. (c) 2006 IMSS. Published by Elsevier Inc.
Keywords: sympathetic skin response; heart rate variability; autonomic dysfunction; fibromyalgia